Simulation results and applications of an advection bounded scheme to practical flows - Ferreira, Valdemir G.; Queiroz, Rafael A. B de; Candezano, Miguel A. Caro; Lima, Giseli A. B.; Corrêa, Laís; Oishi, Cassio M. [UNESP]; Santos, Fernando Luiz Pio dos [UNESP] (Sociedade Brasileira de Matemática Aplicada e Computacional, 2012)
This paper reports experiments on the use of a recently introduced advection bounded upwinding scheme, namely TOPUS (Computers & Fluids 57 (2012) 208-224), for flows of practical interest. The numerical results are compared against analytical, numerical and experimental data and show good agreement with them. It is concluded that the TOPUS scheme is a competent, powerful and generic scheme for complex flow phenomena. Mathematical subject classification: Primary: 06B10; Secondary: 06D05.
Keywords: convection term discretization; convective upwinding scheme; Navier-Stokes equations; Euler equations; time-dependent fluid flow; advection modelling